Bottom-induced contributions to Higgs plus jet at next-to-next-to-leading order - Roberto Mondini; Ciaran Williams (Journal of High Energy Physics, 2021)
Abstract We present a next-to-next-to-leading order (NNLO) QCD calculation of the bottom-induced contributions to the production of a Higgs boson plus a jet, i.e. the process pp → H + j to O y b 2 α s 3 $$ \mathcal{O}\left({y}_b^2α_s^3\right) $$ . We work in the five-flavor scheme (5FS) in which the bottom quark mass is retained only in the coupling to the Higgs boson. Our calculation uses N-jettiness slicing to regulate infrared divergences, allowing for fully-differential predictions for collider observables. After extensively validating the methodology, we present results for the 13 TeV LHC. Our NNLO predictions show a marked improvement in the overall renormalization and factorization scale dependence, the latter of which proves to be particularly troublesome for 5FS calculations at lower orders. In addition, using the same methodology we present a NNLO computation of b b ¯ $$ b\overline{b} $$ → H. Our results are implemented into MCFM.